Short Notices (Reviews in religion and theology, 2004)
Books reviewed: Legitimating New Religions, James R. Lewis, Rutgers University Press 2003 (0-8135-3324-4), pp. viii + 272, Pb $21.95 Dictionary of Buddhism, Damien Keown with contributions from Stephen Hodge, Charles Jones and Paola Tinti, Oxford University Press 2003 (0-19-860560-9), pp. x + 357, Hb £20/$35 The Bible: The New Revised Standard Version Cross-Reference Edition, with Apocrypha; Anglicized Text, Managing Editor Martin H. Manser, with John Barton (for the Old Testament) and Bruce Metzger (for the Apocrypha and New Testament), Oxford University Press 2003 (0-19-100016-7), pp. xxii +1,520, Hb £35 When the Great Abyss Opened: Classic and Contemporary Readings of Noah's Flood, J. David Pleins, Oxford University Press 2003 (0-19-515608-0), pp. xi + 242, Hb £20 Exploring the Old Testament, Volume 3: The Psalms and Wisdom Literature, Ernest Lucas, SPCK 2003 (0-281-05431-2), pp. xvi + 207, Pb £16.99 Who Were the Early Israelites and Where Did They Come From?, William G. Dever, Eerdmans 2003 (0-8028-0975-8), pp. xi + 268, Pb £17.95 Paul, Luke and the Graeco-Roman World: Essays in Honour of Alexander J. M. Wedderburn, Alf Christophersen, Carsten Claussen, Jörg Frey and Bruce Longenecker (eds), Journal for the Study of the New Testament Supplement Series 217, Sheffield Academic Press 2002, A Continuum Imprint (1-84127-259-0), pp. xvi + 290, Hb £65 God and History in the Book of Revelation: New Testament Studies in Dialogue with Pannenberg and Moltmann, Michael Gilbertson, Cambridge University Press 2003 (0-521-82466-4), Society for New Testament Studies Monograph Series 124, pp. xiii + 235 Hb £47.50/$65 From Dogma to History: How Our Understanding of the Early Church Developed, William H. C. Frend, SCM Press 2003 (0-334-02908-2), pp. vii + 212, Pb £12.99 Richard Hooker and Reformed Theology: A Study of Reason, Will, and Grace, Nigel Voak, Oxford University Press 2003 (0-19-926039-7), pp. xviii + 348, Hb £50/$85 Nice and Hot Disputes: The Doctrine of the Trinity in the Seventeenth Century, Philip Dixon, Continuum 2003 (0-5670-8816-2), pp. xi– 236, Hb £40 Christian Mystics: Their Lives and Legacies Throughout the Ages, Ursula King, Routledge 2004 (0-415-32652-4), pp. v + 270, Pb £13.99 The Blackwell Companion to Political Theology, Peter Scott and William T. Cavanaugh (eds), Blackwell 2004 (0-631-22342-8), pp. x + 566, Hb £85 Progressive Christians Speak: A Different Voice on Faith and Politics, John Cobb Jr (ed.), Westminster John Knox Press 2004 (0-664-22589-6), pp. xvi + 341, Pb £20 War and Peace: A Selection of Key Readings. Problems in Theology 3, Jeff Astley, David Brown and Ann Loades (eds), T. & T. Clark 2003, A Continuum Imprint (0-567-08973-8), pp. viii + 111, Pb £12.99 Invitation to the Sociology of Religion, Phil Zuckerman, Routledge 2003 (0-415-94126-1), pp. ix + 156, Pb £15.99 Faith and Feminism: An Introduction to Christian Feminist Theology, Nicola Slee, Darton, Longman and Todd 2003 (0-232-52486-6), Exploring Faith: Theology for Life, pp. xi + 131, Pb £8.95 Introducing Feminist Perspectives on Pastoral Theology, Zoë Bennett Moore, Introductions in Feminist Theology 11, Sheffield Academic Press 2002, A Continuum Imprint (0-8264-6261-8), pp. 157, Pb £15.99/$11.90 Teaching Freud Diane Jonte-Pace (ed.), Oxford University Press 2003 (0-19-5157680), AAR Teaching Religious Studies Series, pp. xi + 276, Pb £48 Blessed are the Cynical: How Original Sin Can Make America a Better Place, Mark Ellingsen, Brazos Press 2003 (1-58743-042-8), pp. 208, Hb $23.99 Worship, Keith F. Pecklers, Continuum 2003 (0-8264-6856-X), pp vi + 234, Pb, £14.99 Worship Seeking Understanding: Windows into Christian Practice, John D. Witvliet, Baker Academic 2003 (0-8010-2623-7), pp. 319, Pb $26.99 Theology at the Eucharistic Table: Master Themes in the Theological Tradition, Jeremy Driscoll, Gracewing 2003 (0-85244-469-9), pp. 251, Pb, £17.99 Confessing Jesus Christ: Preaching in a Postmodern World, David J. Lose, Eerdmans 2003 (0-8028-4983-0), pp. viii + 264, Pb £19.99 Charis and Charisma: David Yonggi Cho and the Growth of Yoido Full Gospel Church, Sung-Hoon Myung and Young-Gi Hong (eds), Regnum 2003 (1-870345-45-2), pp. xi + 217, Pb £19.99